1994
DOI: 10.1002/pola.1994.080320805
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional polymerization of supramolecular assemblies: Synthesis and bilayer polymerization of lipids containing α‐methylene‐substituted acyl chains

Abstract: Polymerization of lipid assemblies may be usefully employed to alter the properties of the assemblies. The possible locations of the reactive group in the lipids include (1) the chain terminus, (2) the head group, and (3) near the lipid backbone. The third strategy yields polymerized assemblies which retain their head group functionality and lipid chain motion. We have designed and synthesized new members of this later category by the use of 2‐methylene‐substituted acyl chains. The main transition temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…188 Other polymers/surfaces that have been modified to yield phosphobetaine structures include siloxanes 189,190 and urethanes. 191,192 O'Brien and co-workers have described the synthesis and bilayer polymerization of phospholipid bilayers 193 as well as primary termination and cross-linking polymerization within the bilayer membranes. Regen and co-workers have described polymerized phosphatidylcholine vesicles 194 as well as reversibly polymerizable thiol-disulfide phosphatidylcholine membranes.…”
Section: N-isopropylacrylamide and N-(phosphorylcholine)-n-(ethylened...mentioning
confidence: 99%
See 1 more Smart Citation
“…188 Other polymers/surfaces that have been modified to yield phosphobetaine structures include siloxanes 189,190 and urethanes. 191,192 O'Brien and co-workers have described the synthesis and bilayer polymerization of phospholipid bilayers 193 as well as primary termination and cross-linking polymerization within the bilayer membranes. Regen and co-workers have described polymerized phosphatidylcholine vesicles 194 as well as reversibly polymerizable thiol-disulfide phosphatidylcholine membranes.…”
Section: N-isopropylacrylamide and N-(phosphorylcholine)-n-(ethylened...mentioning
confidence: 99%
“…Similarly, Letourneru, Douzon, and Jozefowicz described the synthesis of a wide range of phosphorylated cross-linked polystyrene derivatives . Other polymers/surfaces that have been modified to yield phosphobetaine structures include siloxanes , and urethanes. , O'Brien and co-workers have described the synthesis and bilayer polymerization of phospholipid bilayers as well as primary termination and cross-linking polymerization within the bilayer membranes. Regen and co-workers have described polymerized phosphatidylcholine vesicles as well as reversibly polymerizable thiol−disulfide phosphatidylcholine membranes. , These structures are particularly interesting due to their potential biodegradability and application as drug carriers.…”
Section: Synthesis Of Polybetainesmentioning
confidence: 99%
“…Many works on the study of syntheses and properties for polymeric phospholipid analogues have been reported from almost 20 years ago. More recently, a series of amphiphilic phospholipid analogous polymers were produced from some hydrophobic acrylamide monomers having two long alkyl chains and a hydrophilic vinyl monomer containing a phosphatidylcholine-like moiety by radical copolymerizations. On the studies of monolayers, those polymers were found to display only the solid analogous phases during the condensed processes.…”
Section: Introductionmentioning
confidence: 99%